RETRACTED: Scientific analysis of the morphological state of cotton varieties in the experiment before defoliation - Ubaydullayev Madaminjon; Usmonov Nodirjon; Mirzaikromov Mirzabobur; To‘xtashev Farrux; Umarqulova Barchinoy; Ergashev Nodirbek (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001